Development of Topical Miltefosine formulations for the treatment of Cutaneous Leishmaniasis - Peralta, Maria Florencia (2021)
Cutaneous leishmaniasis (CL) is a neglected tropical disease endemic in ~90 countries, with an increasing incidence. Presently available pharmacotherapy implies the systemic administration of moderately/very toxic drugs. Miltefosine (Milt) is the only FDA approved drug to treat CL via the oral route (Impavido®). It produces side effects; in particular, teratogenic effects are of concern. A topical treatment would have the great advantage of minimising the systemic circulation of the drug, preventing side effects. We prepared dispersions containing Milt and liposomes to modulate trans-epidermal penetration and evaluated in vivo efficacy. Treatments were topically administered to BALB/c mice infected with Leishmania (Leishmania) amazonensis. The dispersions containing 0.5 % Milt eliminated 99 % of the parasites and cured the lesions with a complete re-epithelisation, no visible scar and re-growth of hair. Fluid liposomes decreased the time to heal the lesion and the time needed to eliminate viable amastigotes from the lesion site. Relapse of the infection was not found one month after treatment in any case. A topical Milt formulation including fluid liposomes seems a promising treatment against CL.